2006
DOI: 10.1002/ijc.21947
|View full text |Cite
|
Sign up to set email alerts
|

Brain cancer mortality and potential occupational exposure to lead: Findings from the National Longitudinal Mortality Study, 1979–1989

Abstract: We evaluated the association between potential occupational lead exposure and the risk of brain cancer mortality in the National Longitudinal Mortality Study (NLMS), which is a prospective census-based cohort study of mortality among the noninstitutionalized United States population (1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989). The present study was limited to individuals for whom occupation and industry were available (n 5 317,968). Estimates of probability and intensity of lead exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 86 publications
0
42
1
Order By: Relevance
“…However, risk of meningioma was consistently increased with all lead exposure metrics for individuals carrying the ALAD2 allele. Previous studies with more rudimentary exposure information have reported an overall increase in meningioma risk with lead exposure (3,(7)(8)(9). Although these studies did not examine possible susceptibility by ALAD genotype, we would expect that if their study populations had only a small proportion of high-risk individuals, lesser magnitudes of overall risk would have been reported than we observed for patients with the ALAD2 allele.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…However, risk of meningioma was consistently increased with all lead exposure metrics for individuals carrying the ALAD2 allele. Previous studies with more rudimentary exposure information have reported an overall increase in meningioma risk with lead exposure (3,(7)(8)(9). Although these studies did not examine possible susceptibility by ALAD genotype, we would expect that if their study populations had only a small proportion of high-risk individuals, lesser magnitudes of overall risk would have been reported than we observed for patients with the ALAD2 allele.…”
Section: Discussioncontrasting
confidence: 65%
“…Whereas some epidemiologic studies have described increased risk of brain tumors with potential lead exposure (3)(4)(5)(6), particularly for meningioma (7)(8)(9), other evaluations report no significant association between lead and brain cancer (10)(11)(12). The inconsistency of previous reports may be due to small numbers of brain tumor cases, limited exposure assessment for lead, or lack of consideration of brain tumor type.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that Pb and Cd are toxic and carcinogenic metals (Nawrot et al, 2002). It has been suggested that Pb has a facilitating role in the carcinogenesis through inhibition of DNA synthesis and repair, oxidative injury and interaction with DNA-binding proteins and tumor suppressor proteins (Inskip et al, 1995;Wijngaarden and Dosemeci, 2006). In humans, increased carcinogenic elements may be associated to a variety of disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, all three heavymetal exposures inhibited plant growth after 15 days. As a known toxicant to organisms, lead can induce various types of toxicity, including genotoxicity, immunotoxicity, and nephrotoxicity, and can inhibit the growth of organisms (Zurich and others 2002;van Wijngaarden and Dosemeci 2006;Jain and others 2007). Conjecturally, lead should inhibit the growth of plants; this was observed in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Among these heavy-metal contaminants, lead and zinc concentrations have been up to 70 and 120 lg L -1 in seawater from the Bohai Sea, respectively (Zhang 2001;Mao and others 2009). Lead is a nonessential element for organisms and causes various toxicities, including neurotoxicity, nephrotoxicity, cardiovascular disease, genotoxicity, immunotoxicity, and carcinogenicity in animals (Zurich and others 2002;van Wijngaarden and Dosemeci 2006;Jain and others 2007). Zinc is essential to organisms; however, excessive Zn can induce potential toxicities such as genotoxicity and immunotoxicity in vertebrates (Hogstrand and Wood 1996).…”
Section: Introductionmentioning
confidence: 99%